2011
DOI: 10.1111/j.1600-0579.2010.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach to improve oral and maxillofacial surgery education

Abstract: To improve teaching quality and student satisfaction, a new curriculum in Oral Surgery was implemented at Karolinska Institutet in 2007. This paper describes the curriculum change as well as the results regarding quality, satisfaction, cost-effectiveness and workload for teachers and staff. To design the new curriculum, all members of the teaching staff participated in a series of group discussions where problems with the previous curriculum were identified and ideas on how to improve the curriculum were discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Furthermore the unaltered patient-flow caused uneven learning conditions and was very stressful for the teachers and assisting staff. A new curriculum was developed where the bulk of observational education was replaced by interactive seminars, improving the course [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the unaltered patient-flow caused uneven learning conditions and was very stressful for the teachers and assisting staff. A new curriculum was developed where the bulk of observational education was replaced by interactive seminars, improving the course [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study support the importance of the clinical teacher as a guide, facilitator, and medical expert as suggested by others 10 , 14 . In a previous study that tested supervision by different professionals in a third molar surgery simulator, feedback given by a teacher had the most favorable impact on learning practical skills for students 1 . Another part of that study found that, when compared to paper‐based cases or patients, the program had the advantage of providing immediate feedback to students, concluding that quick feedback was of great importance for effective learning 6 …”
Section: Discussionmentioning
confidence: 99%
“…Today, patients increasingly demand that students treating them have prior practical training. In addition, a study in which the oral surgery curriculum was changed from traditional education to interactive learning found that cost‐effectiveness and student satisfaction increased 1 . Nevertheless, the gap between theoretical knowledge and practice in the surgery theater remains wide.…”
mentioning
confidence: 99%
“…They proposed that CAI efficacy can be improved if adaption to learner's cognitive and learning styles is taken into account. In a recent study, we have found that dental students were more like doers than analysts . However, all kinds of students need supervision, but as OMS specialists are costly to use in education, we wanted to investigate whether other types of supervisors would suffice.…”
Section: Introductionmentioning
confidence: 99%